Micronuclear genome organization in Euplotes crassus: a transposonlike element is removed during macronuclear development. - Baird, S E (1989)
After mating, hypotrichous ciliated protozoa transform a set of their micronuclear chromosomes into thousands of short, linear DNA molecules that form the macronuclear genome. To examine micronuclear genome organization in the hypotrich Euplotes crassus, we have analyzed two cloned segments of micronuclear DNA as well as the macronuclear DNA molecules that are derived from them. E. crassus was found to display a number of features characteristic of other hypotrich genomes, including (i) clustering and close spacing of the precursors of macronuclear DNA molecules, (ii) the frequent occurrence of internal eliminated sequences within macronuclear precursors, (iii) overlapping macronuclear precursors, (iv) lack of telomeric repeats at the ends of macronuclear precursors, and (v) alternative processing of the micronuclear chromosome to yield multiple macronuclear DNA molecules. In addition, a moderately repetitive, transposonlike element that interrupts the precursors of two macronuclear DNA molecules has been identified and characterized. This transposonlike element, designated Tec1, is shown to be reproducibly removed from one of the macronuclear precursors during independent episodes of macronuclear development.